River Cleaning Action Program As A Strategy To Improve Sanitation In Gajah Ayee Village, Sigli City - Delfian Masrura; Arrazy Elba Ridha; Fitry Hasdanita; Desi Marliza; Julia Rizki; Meylis Safriani; Alfisyahrin Alfisyahrin (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
This community service project aims to address environmental degradation in Gajah Ayee Village, Aceh, caused by the practice of disposing of household waste into rivers, which leads to clogged waterways and health risks. The project employed a participatory approach (PAR) and was carried out from February 5–25, 2026. The activities involved 32 participants from the PKK, village officials, and coastal residents. The phases included preparatory coordination, physical cleanup activities, structured environmental education, and follow-up cleanup after the education sessions. The results of the community service project included physical actions that successfully removed approximately 460 kg (30 sacks) of waste. Inorganic waste was transported to a landfill, while organic waste was processed into compost to avoid open burning. An evaluation showed a significant increase in community awareness, as residents began sorting their waste and no longer disposed of it in the river. The integration of concrete action and cognitive education effectively transformed the community’s perception of the river as a vital asset rather than a dumping ground. Recommendations for follow-up include the provision of segregated waste collection facilities by the Environmental Agency (DLH) and a regular waste pickup system.